Anemia status, knowledge level, attitude and motivation of anemic adolescent girls in school-based educational interventions in Jambi City, 2025 - Ibnu, Ismi Nurwaqiah; Guspianto; Meinarisa; Pramudiani, Dessy (Proceedings Academic Universitas Jambi, 2025)
Background: Anemia among adolescents is influenced not only by nutritional deficiencies but also by limited knowledge, attitudes, and perceptions related to anemia prevention. Objective: This study aimed to evaluate the effectiveness of a school-based nutrition education intervention using a behavioral change approach among adolescent girls in Jambi City. Methods: A quasi-experimental design was employed involving 65 participants divided into an intervention group (n=37) and a control group (n=28). All participants were screened for anemia (hemoglobin <12 g/dL) and assessed for knowledge, attitude, motivation, and nutritional intake at baseline and post-intervention. The control group received standard anemia prevention modules, while the intervention group participated in the “8000 Days Against Anemia Club,” a six-week program combining lectures, games, peer counseling, and practical activities. Results: Statistical analysis using the t-test showed that the intervention significantly reduced anemia prevalence from 100% to 7.1% and increased mean hemoglobin levels by approximately 2 g/dL, while the control group retained a high anemia prevalence of 78.4%. In addition, the intervention group demonstrated marked improvements in knowledge, attitudes, and motivation toward anemia prevention. Conclusion: These findings indicate that participatory, school-based educational approaches effectively enhance awareness and produce measurable biological impacts in reducing anemia among adolescent girls.